The European Profiling Grid (EPG) Pre-service Teachers’ Level in Lesson and Course Planning Competence - Nurkhamidah, Neni (Scientia: Jurnal Hasil Penelitian, 2024)
The quality of teachers significantly influences student performance, making it crucial for educators to possess the necessary competencies to be effective. This study assesses the competencies of prospective teachers from the English Department at Media Nusantara Citra University using The European Profiling Grid (EPG), which mandates that graduates achieve at least the beginner teacher level. The research aims to evaluate these prospective teachers' abilities in lesson planning and teaching according to EPG standards. Using a qualitative descriptive method, the study involved 17 students undergoing Field Practice (PKL), with data collected from their lesson plans and interviews. Results reveal that 13 prospective teachers were at the beginner level, while 4 reached the experienced teacher level. The findings indicate that all participants met the minimum graduation requirements based on EPG, specifically in lesson planning and teaching competencies.